2019
DOI: 10.1186/s12989-019-0299-z
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Toxicity and Immunological Effects of Carbon-based Nanomaterials

Abstract: Background Carbon nanomaterials are a growing family of materials featuring unique physicochemical properties, and their widespread application is accompanied by increasing human exposure. Main body Considerable efforts have been made to characterize the potential toxicity of carbon nanomaterials in vitro and in vivo. Many studies have reported various toxicology profiles of carbon nanomaterials. The different results of the cytotoxicity of the carbon-based materials mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
209
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 320 publications
(215 citation statements)
references
References 169 publications
(232 reference statements)
3
209
0
3
Order By: Relevance
“…Generally speaking, carbon‐based materials are inherently less toxic than metal‐ or semiconductor‐based materials considering the nature of carbon. Still, cytotoxicities of carbon‐based nanomaterials have been reported in various studies . For example, Magrez and co‐workers have shown that carbon nanomaterials such as MWCNTs, carbon nanofibers, and carbon NPs are toxic.…”
Section: Biosafety and Biodistribution Of Carbon‐based Nanomaterialsmentioning
confidence: 99%
“…Generally speaking, carbon‐based materials are inherently less toxic than metal‐ or semiconductor‐based materials considering the nature of carbon. Still, cytotoxicities of carbon‐based nanomaterials have been reported in various studies . For example, Magrez and co‐workers have shown that carbon nanomaterials such as MWCNTs, carbon nanofibers, and carbon NPs are toxic.…”
Section: Biosafety and Biodistribution Of Carbon‐based Nanomaterialsmentioning
confidence: 99%
“…Cell viability was much better in the medium and low concentration range, as opposed to the high concentration range. Yuan and colleagues evaluated the effects of MWCNTs on macrophages and found that long MWCNTs were more toxic than short MWCNTs [29]. As these carbon nanotubes were suspended in culture medium and ultrasonicated prior to use, the toxicity could be due to the fact that CNTs were not functionalized.…”
Section: Neurocompatibility Of the Mwcntsmentioning
confidence: 99%
“…Previous studies evidenced that multiwall carbon nanotubes caused a significant time-and dose-dependent decrease in cells' viability [42,43], and that they could be toxic at sufficiently high concentrations. Indeed, it was reported that carbon nanomaterials present significantly different cytotoxicity depending on their physicochemical properties, including size, length, shape, and surface area [44][45][46]. The lack of filler coalescence, defined as a consequence of CNF incorporation, suggested the constitution of an improved UHMWPE-based material, in which the absence of debris could favour the slowing down of inflammatory and oxidative stress effects commonly ascribed to these materials [47][48][49][50][51][52].…”
Section: Cytotoxicitymentioning
confidence: 99%